Design Of Health Service Mobile Application Interface Using User Centered Design Method - Dewi, Berliana Kemala; Defriani, Meriska; Sunandar, M. Agus (Politeknik Ganesha Medan, 2023)
: In this modern era, many things that have been digitized indirectly help in community activities, especially in obtaining public service facilities. This clinic is one of the public facilities in Purwakarta Regency which is engaged in health services to facilitate services to the community. One of the efforts of this Clinic is to continue to provide effective and efficient health facilities under any circumstances and aims to increase the attractiveness of patients to the clinic. The purpose of this research is to design a health service mobile application interface using the User Centered Design method to provide health service information to the general public. User centered design is a design process that focuses on user needs, by carrying out 5 stages, namely Understand Context of Use, Specify User Requirements, Design Solutions, Evaluate Against Requirements. Products developed using this method are optimized for users and emphasized on how the user needs or wants to use a product. Interface testing uses the Single Ease Question as a measure of the success rate of interface design that has been made. The results of this study resulted in an interface design that is in accordance with the characteristics of the general public, this is evidenced by the results of the evaluation using the Single Ease Question getting an average score of 6.7 out of 5 assignments given to 5 respondents during the testing stage, so it can be concluded that the score It has a good level of convenience and is easy to use.